TRACE ELEMENT AND ISOTOPE EVOLUTION DURING CONCURRENT ASSIMILATION, FRACTIONAL CRYSTALLIZATION, AND LIQUID IMMISCIBILITY OF A CARBONATED SILICATE MAGMA - Ray J.S. (My University, 1998)
Liquid immiscibility is an important magmatic process that causes unmixing of magmas into liquids of contrasting compositions. Such magmas may get modified by simultaneous wall rock assimilation and fractional crystallization during the liquid immiscibility in a crustal magma chamber. The element and isotope effects of such a process are likely to be reflected in the final products. To treat these effects and to understand the evolution of the immiscible liquids, a model has been developed modifying the assimilation-fractional crystallization (AFC) model of I demonstrate the applicability of this model by an example using Sr isotope systematics of silicate-carbonate melt immiscibility. The initial 87 Sr/ 86 Sr ratio and Sr concentration variation in the silicate rocks of some alkaline-carbonatite complexes of Deccan Province are found to be a result of lower crustal contamination (up to 5%) of the parent carbonated silicate magma, while the 87 Sr/ 86 Sr of the carbonate melt separated out of the parent remained unaffected. Though the data on silicate rocks could also be explained by the conventional AFC model, the processes treated by the model do not include liquid immiscibility, needed for explaining the evolution of the cogenetic carbonatites. It appears from this study that the slightly higher initial 87 Sr/ 86 Sr (than that of the coexisting carbonatites) shown by the alkaline silicate rocks could be due to crustal contamination of the carbonated silicate parent magma during concurrent fractional crystallization of silicates and exsolution of carbonate melt. Though the model has been applied to a very specific case--that of carbonate-silicate melt immiscibility--it can be applied to any case in which both assimilation and immiscibility occur together.